The Art of Nonfction No. 11. - Gordon-Reed, Annette (Paris Review)
An interview with Annette Gordon-Reed, author of the book "Thomas Jefferson and Sally Hemmings: An American Controversy," is presented. Gordon-Reed talks about the confidence and drive she had which came from her parents, when Thomas Jefferson first caught her imagination, and whether she learned her research methods while she was practicing law.